(untitled) (Biological Sciences - PJSIR, 2021)
Salinity hampers the production of many field crops in the region including rice (Oryza sativa L.), while commonly classified as salt sensitive within the same species, the level of sensitivity varies between genotypes. This study investigated the salinity tolerance of 28 rice genotypes, including 9 aromatics and 19 non-aromatics. Sixty seeds of each genotype were initially sown in trays (24x18 inches) during the 1st week of June, by of using four salt treatments (0, 40, 80 and 120 mM NaCl+CaCl2 @ 20:1). The experiment was laid down in a completely randomized design with four replicates in laboratory conditions, at Shah Abdul Latif University Khairpur, Sindh, for the period of twenty-five days. A significant reduction in agro-morphological parameters was observed against all salinity levels. Based on reduction in dry matter yield, all rice genotypes were found tolerant at 40 mM. Eleven rice genotypes were found tolerant, fourteen were moderately tolerant, one was moderately sensitive and remaining two genotypes were found sensitive at 80 mM salinity level. Furthermore, none of the genotypes were able to with stand 120 mM of salinity. The genotypes Khushboo, DR-83 and Mahek performed meager and showed more than 50% reduction over control and categorised as sensitive, with the genotypes Latifee, DR-67 and DR-92, DR-51 and IR-6 are categorised as tolerant with a reduction of less than 20% over control based on dry matter yield reduction against all salinity treatments at the early seedling stage. However, these genotypes cannot be justified as tolerant only on the basis of their improved performance at early growth stage. Hence, these genotypes are suggested to be studied further at other advanced growth stages up to maturity to evaluate their response under a saline environment.